﻿Divergent karyotypes in five genera of the African endemic fish family Distichodontidae (Cithariniformes, Osteichthyes) - Sergey A. Simanovsky; Dmitry A. Medvedev; Fekadu Tefera; Alexander S. Golubtsov (Comparative Cytogenetics, 2023)
The African family Distichodontidae comprises 109 species in 16 genera. Up-to-date cytogenetic information was available for the only distichodontid species Distichodus affinis Günther, 1873. Here we report chromosome number and morphology in: Distichodus engycephalus Günther, 1864 (2n = 52, FN = 104), Ichthyborus besse (Joannis, 1835) (2n = 46, FN = 92), Nannocharax niloticus (Joannis, 1835) (2n = 54, FN = 106) and three taxa, Nannaethiops bleheri Géry et Zarske, 2003, Nannaethiops sp., and Neolebias unifasciatus Steindachner, 1894, that exhibit the same karyotypes (2n = 50, FN = 98). To confirm the Nannaethiops Günther, 1872 and Neolebias Steindachner, 1894 species identification, mt-DNA sequences of the two markers (COI and 16S rRNA) were obtained from karyotyped specimens and compared with the relevant sequences accessible from GenBank. The great prevalence of biarmed chromosomes (the karyotypes of most species contain exclusively biarmed chromosomes) is a distinctive characteristic of Distichodontidae and Cithariniformes as a whole.